2022
DOI: 10.3390/ijms23052428
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into the Serum Sphingolipid Fingerprint Characterizing Longevity

Abstract: Sphingolipids (SLs) are structural components of the lipid bilayer regulating cell functions. In biological fluids, their distribution is sex-specific and is at variance in aging and many disorders. The aim of this study is to identify SL species associated with the decelerated aging of centenarians. SLs, extracted from serum of adults (Ad, 35–37 years old), aged (Ag, 75–77 years old) and centenarian (C, 105–107 years old) women were analyzed by LC-MS/MS in combination with mRNA levels in peripheral blood mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Together, these data support a model where increased abundance of sphingolipid precursors and sphingomyelin may contribute to poor aging phenotypes. Indeed, our findings support lipidomic analyses of human longevity suggesting that centenarians upregulate mechanisms to upregulate sphingomyelins to ceramide-containing glycosphingolipids [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 81%
“…Together, these data support a model where increased abundance of sphingolipid precursors and sphingomyelin may contribute to poor aging phenotypes. Indeed, our findings support lipidomic analyses of human longevity suggesting that centenarians upregulate mechanisms to upregulate sphingomyelins to ceramide-containing glycosphingolipids [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 81%
“…Notably, depletion of Es resulted in a significant increase in total Cer levels while S1P decreased significantly, further strengthening the role of Es as a bridge between SLs and CV system homeostasis. The importance of the aging process on SL release in women has been recently reported by our group [ 170 ]. In particular, we characterized for the first time the serum SL profile in adults (35–37 years old) vs. aged (75–77 years old) vs. long-lived (centenarians; 105–107 years old) women and in accordance with previous results we observed that Cer levels increased with age.…”
Section: Estrogens and Sphingolipidsmentioning
confidence: 60%